Diversity of bird species in the coffee agroforestry landscape: Case study in the Pangalengan Sub-district, Bandung District, West Java, Indonesia - SUSANTI WITHANINGSIH; PARIKESIT; RIZKA FATHARANI ALHAM (Society for Indonesian Biodiversity, 2020)
Abstract. Withaningsih S, Parikesit, Alham RF. 2020. Diversity of bird species in the coffee agroforestry landscape: Case study in the Pangalengan Sub-district, Bandung District, West Java, Indonesia. Biodiversitas 21: 2467-2480. Traditionally, shade-grown coffee agroforestry is home to diverse taxa, including insects and mammals. However, research has shown that shade-grown coffee agroforestry is also an important habitat for various types of birds. A study on the diversity of bird species was performed in the coffee agroforestry landscape area of Perum Perhutani, Pangalengan Sub-district, Bandung District, West Java. Bird diversity data was collected using the point count method, and landscape structure analysis was performed, to quantify the characteristics of the landscape. The results were analyzed using Pearson's correlation analysis to determine the relationships between landscape structures and bird species diversity. The results of the study recorded 60 species of birds, from 29 families, among 1,581 individuals. The most dominant bird species were Pycnonotus aurigaster, Orthotomus sutorius, Orthotomus ruficeps, Streptopelia chinensis, and Brachypteryx leucophrys. The highest species abundance value at the research site was recorded for Pycnonotus aurigaster, with a relative abundance value of 22.02%. The diversity of bird species found at the study location was classified as high (H ' = 3.10). Thus, coffee agroforestry landscapes are associated with bird diversity, and diversity appears to increase when the total area (TA) increases; however the patch edge length (TE), number of spots (NP), the complexity of patch forms (MSI, MPFD) and landscape heterogeneity (SHDI) decrease. The coffee agroforestry landscape may represent an important habitat for many bird species.